Description of second and third instar larvae of Cuterebra histrio Coquillett, 1902 and first report of Metacuterebra apicalis (Guérin-Ménéville, 1835) (Diptera: Oestridae) in Veracruz, Mexico - Lara-Lagunes, Nora; Jaume-Schinkel, Santiago; Ibáñez-Bernal, Sergio (Instituto de Ecología, A.C., 2022)
In this work we describe and illustrate for the first time the second and third instar of the rodent bot fly Cuterebra histrio Coquillett, 1902, furthermore, we discuss morphological characters that can be helpful in the identification of larvae of different species. Additionally, we report for the first time the species Metacuterebra apicalis (Guérin-Ménéville, 1835) for the state of Veracruz, Mexico.